The Diagnostics of Disease Relapse Within Five-Year Follow-Up and the Role of Androgen Receptor Expression in Patients with Early Triple-Negative Breast Cancer - Igor Spurnić; Snežana Šušnjar; Irena Jovanić; Nataša Medić-Miljić; Zorka Milovanović; Marina Popović Krneta; Zoran Bukumirić; Dušica Gavrilović; Saša Rajšić; Ivan Marković (Diagnostics)
Background/Objectives: Triple-negative breast cancer (TNBC) is characterized by the absence of the expression of estrogen receptors, progesterone receptors, and human epidermal growth factor receptor 2. As there are no specific targeted therapies, TNBC patients often face an aggressive clinical course. The expression of the androgen receptor (AR) has been found in up to 30% of TNBC cases, but the association between the AR status and survival rates in TNBC remains controversial. The aim of this study was to explore the association of AR expression with the disease outcome in patients with early TNBC within a 5-year follow-up. Methods: AR expression was determined by immunohistochemistry in a cohort of 124 early-TNBC patients treated at the Institute for Oncology and Radiology of Serbia. The cut-off value used for the positive AR status was >10% tumor cells. The association of the AR status with clinicopathological factors (age, stage, tumor diameter, lymph node invasion, metastatic spread, Ki-67 score, EGFR score, and cytokeratin 5/6 score) and the disease outcome (disease-free survival—DFS—and overall survival—OS) was investigated. Results: Our analysis showed that the AR-positive status was associated with a significantly lower Ki-67 score compared to the AR-negative samples. A univariate analysis indicated that the age, tumor size, nodal status, and EGFR score significantly influenced both 5-year DFS and OS. Multivariate Cox analysis suggested that a smaller tumor size, lower nodal status, and AR expression were independent predictors of longer survival rates in TNBC patients. Conclusions: The results of this study suggest that the positive AR status may be a favorable prognostic factor in TNBC patients within the first five years after surgery.